Specialized ceramic production at Tell el Far’ah North: the metallic ware - Gondim, Letícia da Silva (2021)
Abstract: This master thesis presents an archaeological study of the Metallic Ware from the Tell elFar'ah North (West Bank) archaeological site, on ceramic fragments dating from the Early Bronze Age II (3000 - 2700 BC). Optical Microscopy and X-ray powder diffraction showed a Metallic Ware different from the North Canaanite one, produced with a calcareous clay with dominant quartz, common fragments of sedimentary and siliceous rocks, few feldspars, and nodules of iron oxides. The Metallic Ware quality was achieved by high firing temperature between 850-900 ºC. Tell el-Far'ah North was hypothesized as one of the main production centres of Metallic Ware.